Herd Immunity to the Measles, Mumps and Rubella Viruses Among the Belgradian Population in May, 2024 - Anna Y. Popova; Vyacheslav S. Smirnov; Svetlana A. Egorova; Luka Dragačević; Angelica M. Milichkina; Jelena Protić; Ekaterina M. Danilova; Irina V. Drozd; Marija Petrušić; Ojuna B. Zhimbaeva; Elizaveta S. Glazkova; Nataša Gutić; et al. (Vaccines)
Background/Objectives: In the Republic of Serbia, measles vaccination was first introduced in 1971, while combined vaccination (measles, mumps, rubella) was made mandatory in 1996 as part of the national vaccination program. Reported prevalence values for 2023 were <0.75 cases per 100K population for measles, 0.09 cases per 100K for mumps, and no cases of rubella. Methods: This cross-sectional study was performed in May, 2024 as part of the project “Herd Immunity to Vaccine-Preventable and Other Relevant Infections in the Belgradian Population.” It focused on assessing herd immunity to measles, mumps and rubella (MMR) among residents insofar as these remain a public concern despite the availability of vaccines. A total of 2533 subjects were distributed across nine age groups, covering those aged 1–70+ years and various professional groups residing in Belgrade. Participants were stratified by age and activity. Upon obtaining individual information by online questionnaire and receiving a signed statement of informed consent, blood samples were obtained for IgG antibody testing (ELISA) to determine MMR serological status. The results were compared to national and international immunization standards to evaluate herd immunity levels. Results: Our results indicate varying levels of immunity for each virus, with specific demographic groups showing different immunity levels. Total measles seroprevalence during this study was 74.7%, with significant variation across all age groups. While high seropositivity was observed in both children (90.7%) and elder age groups (98.4%), middle-aged individuals in the age group 30–49 years showed significantly lower IgG levels. Between 2021 and 2023, there were no registered cases of rubella detected in Serbia, which indicates a high level of immunity. This was confirmed here with consistently high IgG levels across all age groups, with an average seropositivity of 94.8%. Average mumps seropositivity across all age groups was 85.1%. The lowest value was in the young child (1–5 years) age group (76.1%); the highest was in the elderly group (92.6%). Conclusions: The current findings suggest that the Belgradian population has strong overall immunity to MMR, yet with some concerns regarding measles immunity in middle-aged adults, suggesting a potential need for catch-up vaccinations. While rubella status indicates strong herd immunity and minimal risk of outbreaks, mumps immunity in some groups (children, middle-aged adults) is below the protective threshold. While it is still sufficient to prevent widespread transmission, it should be closely observed. To our knowledge, this study is the first of its kind to provide data about MMR seroprevalence in Belgrade. Findings indicate the need for constant surveillance and revaccination of vulnerable/seronegative groups.